The impact of a college career intervention program on career decision-making self-efficacy, career indecision and decision-making difficulties - Lam, Michele; Santos, Angeli (SAGE, 2017)
A quasi-experimental longitudinal intervention study utilizing intervention and comparison groups was carried out with first-year Malaysian college students in order to evaluate the effectiveness of a careers course designed to help students in their career decision making. Participants in both groups were given questionnaires assessing career decision self-efficacy, career indecision and career decision-making difficulties at various time points. Career indecision and decision-making difficulties are different constructs in that research on career indecision encompasses a wider area wherein the identification of sources of career indecision, often referred to as decision-making difficulties, is one line of research. Gender differences at the outset and over the duration of the course were also examined. Results indicated that upon completion of the course participants in the intervention group experienced increased career decision self-efficacy and reduced career indecision compared to the comparison group. An overall decrease in career decision-making difficulties was also observed but further investigation revealed that the decrease was not significant in one of 10 subcategories of difficulties. Although gender differences in career indecision and career decision making difficulties were observed at the outset, these disappeared over the course of the intervention. Implications and suggestions for further research are discussed.